1993
DOI: 10.3171/jns.1993.78.2.0226
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal baclofen for intractable spasticity of spinal origin: results of a long-term multicenter study

Abstract: A total of 93 patients with intractable spasticity due to either spinal cord injury (59 cases), multiple sclerosis (31 cases), or other spinal pathology (three cases) were entered into a randomized double-blind placebo-controlled screening protocol of intrathecal baclofen test injections. Of the 88 patients who responded to an intrathecal bolus of 50, 75, or 100 micrograms of baclofen, 75 underwent implantation of a programmable pump system for chronic therapy. Patients were followed for 5 to 41 months after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
205
0
11

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(223 citation statements)
references
References 24 publications
7
205
0
11
Order By: Relevance
“…3 The decision to implant a drug delivery system is usually taken after a positive test (two points diminution in Ashworth or Spasm frequency scale) obtained after a single injection of 50-100 mg of intrathecal baclofen. 3,4 The effect on the spasticity is spectacular in most cases with a quick diminution of the muscle tonus. [4][5][6] Quality of life usually improves due to decrease of nocturnal spasms and a better level of independence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The decision to implant a drug delivery system is usually taken after a positive test (two points diminution in Ashworth or Spasm frequency scale) obtained after a single injection of 50-100 mg of intrathecal baclofen. 3,4 The effect on the spasticity is spectacular in most cases with a quick diminution of the muscle tonus. [4][5][6] Quality of life usually improves due to decrease of nocturnal spasms and a better level of independence.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The effect on the spasticity is spectacular in most cases with a quick diminution of the muscle tonus. [4][5][6] Quality of life usually improves due to decrease of nocturnal spasms and a better level of independence. 6,7 As therapeutic doses are low, the treatment is usually well tolerated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies with intrathecal baclofen have also noted increasing dosage requirements with the passage of time. 1,5,8,33 This has been attributed to the downregulation of GABA-B receptors at the spinal level. 1,33 In our study, the slight increase in tone at 12 months is also suggestive of emerging tolerance.…”
Section: Dosage Requirementsmentioning
confidence: 99%
“…Previous studies have found catheter malfunction occurring at rates varying from 10% to 40%. 2,3 Kink and perforation represent 50% of the causes of catheter malfunction. A plain X-ray is usually enough to show a dislodgement or a kink.…”
Section: Introductionmentioning
confidence: 99%